Lesni odpadki in biomasa: pravna ureditev v Sloveniji in Nemčiji - Vimpolšek, Boštjan (Gradbeni vestnik, 2014)
This paper addresses wood waste for reuse and recycling. It includes a review of literature and legislation. Since the legislation is closely related with the management of waste wood and biomass, European directives, which are connected to this field, were studied. To achieve a better analysis, insights, the interpretations of national laws and proceedings the Slovenian and German directives were compared. It has been found that this fieldis becoming increasingly important in Europe. A number of European directives are in force that define the substance of wood waste or biomass and are substantially implemented in many Slovenian and German laws.The Slovenian and the German laws are in some respects similar and in others very different. The German laws compared to the Slovenian ones are more detailed and specified and regulate the legal scope of waste wood and biomass. Nevertheless, it has been concluded that in the legal field of both Member States lies a considerable potential to promote the greater use of wood, such as reused material.
Keywords: biomasa; biomass; Germany; legislation; lesni odpadki; Nemčija; Slovenia; Slovenija; waste wood; zakonodaja